ANALISIS EKONOMI PEMANFAATAN LIMBAH CAIR DI KEBUN SAWIT SEI MANDING, RIAU - Maryadi, Maryadi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
The growth of the oil palm industry in Indonesia has been phenomenal. With only 106.000 ha planted in 1968, it has increased to more than 3,393 million ha in 2000. Fertilizer has played a major role in contributing to the advancement of sustainable oil palm yields. Currently with Asian economies experiencing an economic slow down and locally with the depreciation of rupiah, fertilizer costs have inevitably gone up causing the increase of production costs. Recently some plantations are trying to use waste water for fertilising purpose since it known that waste water contains some potential nutrient such as N, P, K and Mg. In Sei Manding this usage increases the production up to 27%.